The Importance of Welfare State Policies in Empowering Older People - Aylin Görgün Baran; Cansu Taşcı (Yaşlı Sorunları Araştırma Derneği, 2024)
The global increase in the older population and the economic crises increase older people poverty and cause a decline in the welfare of older people. Since appropriate policies cannot be developed by states, older individuals all over the world live in unequal conditions and poverty, deprived of many rights compared to other population groups. This situation requires countries to review their policies on this issue. This study focuses on the importance of developing an empowerment policy in increasing the welfare of older individuals, both individually and publicly, in order to establish older welfare. In this context, the subject of this study is to investigate the role and importance of welfare state policies in increasing the welfare of the older people. This study aims to reveal which welfare policies are effective in improving the welfare of older people. The study includes an evaluation of the relevant literature review. The article seeks answers to the questions of which criteria play a role in the welfare of older people, which models and countries are relatively the most successful in the implementation of differ-ent welfare state regimes and which welfare model Turkey is included in. According to the data ob-tained, it has been determined that the most successful model among the 4 different types of welfare state models is the "social democratic welfare state" and this is seen in the practices of Northern Euro-pean countries. On the other hand, it has been seen that Turkey's disorganized and fragmented older people welfare practices correspond to the Southern European Welfare Regime model (GAR Regime) and are characterized by inequality and discrimination. As a result, it is suggested that instead of im-plementing neo-liberal policies, Esping-Andersen's social welfare state model should be emphasized in the improvement of older people welfare in Turkey.